“Linajes de embustes”: cargas de centurias y tiempos universales en el mundo maya colonial - Mario Humberto Ruz (Journal de la Société des Américanistes)
The encounter with the West and the imposition of new chronological and chronometric parameters, forced the Maya culture –always fascinated by the conception and recording of time–, to adjust its parameters to the beliefs of its Spanish conquerors. Among the different strategies implemented, we can point out the redefinition of their ancient measurement system and the inclusion of their own historical events and processes within the providential and supposedly universal perceptions that characterized the Christian concepts brought by the Spaniards.